A two-seater light-weight solar powered clean car: preliminary design and economic analysis - Ahmed, Sanjana; Zenan, Ahmed Hosne; Rahman, Mosaddequr Abdur (© 2014 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 3rd International Conference on the Developments in Renewable Energy Technology, ICDRET 2014; Dhaka; Bangladesh; 29 May 2014 through 31 May 2014 [© 2014 Institute of Electrical and Electronics Engineers Inc.] The conference paper's website available at: http://ieeexplore.ieee.org/document/6861646/